Choosing a class IC antiarrhythmic drug for the treatment of patients without structural heart disease: clinical advantages of the most common agents (literature review) - Sydorova, N. M.; Kolesnyk, M. Yu.; Сидорова, Н. М.; Колесник, Михайло Юрійович (Запорізький державний медико-фармацевтичний університет, 2025)
Aim: to analyze the pharmacological features and updated evidence-based medicine data of Class IC antiarrhythmic drug (AAD) ethacizine compared to propafenone to optimize the choice of treatment for cardiac arrhythmias in patients without structural heart disease. Materials and methods. According to the purpose, a search was conducted for available scientific literature with an emphasis on publications of the last 5 years. We also analyzed scientific information on scientific platforms of the European Society of Cardiology (ESC 365) and the Association of Cardiologists of Ukraine. Results. At first glance, Class IC AADs seem to be identical in the mechanism of action, which creates certain difficulties for practicing physicians when choosing AAD of this class for the treatment of arrhythmias in each specific case. Ethacizine and propafenone were chosen for comparison as the most frequently used Class IC AADs in our country. We presented data from studies comparing the efficacy and safety of the selected AADs with an emphasis on recent studies of ethacizine, as a less well-known AAD in Europe and globally. In addition, this article includes the main design features of new studies on real-world clinical use of Class IC AADs, including use as a “pill-in-the-pocket” for restoring sinus rhythm in patients with atrial fibrillation (ETERNITY study) and comparing the efficacy of propafenone and ethacizine in maintaining sinus rhythm in patients with paroxysmal and persistent forms of atrial fibrillation. Мета роботи – проаналізувати фармакологічні особливості й оновлені дані доказової медицини щодо антиаритмічного препарату (ААП) ІС класу етацизину порівняно з пропафеноном для оптимізації лікування порушень серцевого ритму у пацієнтів без структурного ураження серця. Матеріали і методи. Здійснили пошук наукової літератури з відкритим доступом, передусім до аналізу залучали публікації за останні 5 років. Крім того, вивчено матеріали, що представлені на наукових платформах Європейського товариства кардіологів (ESC 365) та Всеукраїнської асоціації кардіологів України. Результати. Препарати ІС класу, на перший погляд, є однаковими за механізмом дії, що створює певні труднощі для лікарів-практиків під час призначення ААП цього класу для лікування аритмій у кожному конкретному випадку. Для порівняння обрано етацизин і пропафенон як ААП ІС класу, що найчастіше застосовують в Україні. Наведено результати досліджень щодо порівняння ефективності та безпеки обраних ААП з акцентом на останніх розвідках з вивчення етацизину як менш відомого в Європі та світі ААП. Наведено основні позиції дизайну нових досліджень, що присвячені вивченню реальної клінічної практики застосування ААП ІС класу, зокрема як «таблетки в кишені» для відновлення синусового ритму при фібриляції передсердь (дослідження ETERNITY), та порівняння ефективності пропафенону та етацизину у підтриманні синусового ритму у пацієнтів із пароксизмальною та персистентною формами фібриляції передсердь.
Вибір антиаритмічного препарату ІС класу для лікування пацієнтів без структурних змін серця: клінічні переваги найпопулярніших засобів (огляд літератури)
Keywords: anti-arrhythmia agents; class IC; ethacizine; propafenone; comparative characteristics; features; антиаритмічні препарати; ІС клас; етацизин; пропафенон; порівняльна характеристика; особливості